Homogeneous antibody-drug conjugates with dual payloads: potential, methods and considerations - Miao Wen; Abigail Yu; Young Park; Daniel Calarese; Hans-Peter Gerber; Gang Yin (mAbs)
The development of site-specific dual-payload antibody-drug conjugates (ADCs) represents a potential advancement in targeted cancer therapy, enabling the simultaneous delivery of two distinct drugs into the same cancer cells to overcome payload resistance and enhance therapeutic efficacy. Here, we examine various methodologies for achieving site-specific dual-payload conjugation, including the use of multi-functional linkers, canonical amino acids, non-canonical amino acids, and enzyme-mediated methods, all of which facilitate precise control over payload attachment while ensuring homogeneity. We explore the implications of different conjugation techniques on drug-to-antibody ratios and the ratios of the two payloads, as well as their impact on process complexity and manufacturability. Additionally, we address the potential advantages of dual-payload ADCs compared to ADCs combined with traditional chemotherapy or single-payload ADC/ADC combinations. By evaluating these innovative methods, we aim to provide a comprehensive understanding of the current landscape in dual-payload ADC development and outline emerging directions necessary for further advancement of this promising therapeutic strategy.